1953
DOI: 10.1021/ja01108a017
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Synthesis of Hydrogen Peroxide at Zinc Oxide Surfaces1

Abstract: Vol. 75 concentration is high. The fates of the heptyl radicals must be diverse, possibly leading to various ketones and aldehydes with seven carbon atoms or less followed by hydrogen abstraction by RO. The presence of unsaturation in the products indicates loss of a second hydrogen by heptyl radicals and also a splitting of these radicals with the formation of short alkyl radicals. This type of reaction does not occur appreciably in the gas phase at room temperature but may be aided in solution by the longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…For a primary alcohol, for instance, the two-equivalent oxidation would be the surface reactions :l RCH20-+ p--> RCHO + H. [14] H'--> H + + e [15] In the case of formate, the first oxidation step would be HCOO-+ p--> CO2 + H. It was assumed that the oxidation of R is two-equivalent and that of X one-equivalent. No chemical analyses were made in order to support this hypothesis.…”
Section: Quenching Of Current Doubling By An Oxidizing Agentmentioning
confidence: 99%
“…For a primary alcohol, for instance, the two-equivalent oxidation would be the surface reactions :l RCH20-+ p--> RCHO + H. [14] H'--> H + + e [15] In the case of formate, the first oxidation step would be HCOO-+ p--> CO2 + H. It was assumed that the oxidation of R is two-equivalent and that of X one-equivalent. No chemical analyses were made in order to support this hypothesis.…”
Section: Quenching Of Current Doubling By An Oxidizing Agentmentioning
confidence: 99%
“…It has long been known that H202 is produced when aqueous ZnO dispersions are irradiated (9) and that the formation of HzOz is enhanced when a suitable donor is added to the system. When DMPO was added to an aqueous ZnO suspension containing no added donors and irradiated (h < 380nm), large quantities of .OH radical adducts were produced.…”
Section: Resultsmentioning
confidence: 99%
“…This was first suggested by Rubin er al. in 1953 (9) in the photogeneration of H,O, in aqueous ZnO dispersions. The present authors have shown that CdS was capable of reducing methyl viologen at the expense of EDTA.…”
Section: Photoelectrophoresis (Pep)mentioning
confidence: 99%
“…Although redox reagents with the highest redox potential were expected to show the highest evolution of O 2 , while those with the lowest redox potential should have shown the highest evolution of H 2 , only a few clear-cut cases were found for the evolution of O 2 . One was H 5 IO 6 , a periodic acid having the highest redox potential while the only other examples found were for IO 3 -, VO 2 + , and BrO 3 -. A series of available redox reagents have been tested as the electron donor in photocatalytic systems for the evolution of H 2 using a non-oxide InP semiconductor.…”
Section: Separate Evolution Of H 2 and Omentioning
confidence: 96%
“…Therefore, applying the principle of water decomposition over photoelectrochemical cells to heterogeneous photocatalytic systems using powdered semiconductors is now a field of great interest, encouraging new fundamental investigations into chemical reactions which take place at the electrode surfaces in the electrochemical cells. Significantly, two experimental improvements have supported these investigations, i.e., the accumulation of data on photocatalytic reactions over powdered semiconductors [3][4][5][6] and developments based on the concept of Bard [7][8][9] which has emerged from studies of photochemical cells with semiconductor electrodes in the design of photocatalytic systems using semiconductor particles or powders, as shown in Fig. 5.…”
Section: Application Of the Honda-fujishima Effect To Powdered Oxidementioning
confidence: 98%